THE STATE AND ETHNIC BOUNDARIES IN SOUTH-EASTERN SIBERIA - Szmyt, Zbigniew (Porównania, 2019)
This paper looks at the long-term process of making and shifting ethnic boundaries in Siberia. I focused on the interdependence of the state, border and ethnicity. During the colonisation of Siberia, the state border functioned as a shifting frontier. The border effect touched mostly indigenous people by keeping them in the radius of a tribute collection system. Later on a system of administrative clans was developed. The Soviet Union brought into the world a quasi-state structure of territorial autonomy for indigenous people and produced modern ethnic elites. Since the 1990s ethnicity has been a key political category and the process of negotiating ethnic boundaries.